FAKTOR-FAKTOR YANG MEMENGARUHI KURS RUPIAH - Raja Rian Ritonga; Hijri Juliansyah; Murtala; Noviami Trisniarti (LPPM Universitas Malikussaleh - Indonesia, 2025)
This study aims to analyze the influence of world CPO prices, money supply, and inflation on the rupiah exchange rate partially or simultaneously in Indonesia from 1993-2023. The research method used in this study is the Autoregressive Distributed Lag (ARDL) Model. This study found that in the short term, world CPO prices have a negative and significant effect on the rupiah exchange rate in Indonesia, while the money supply and inflation have a positive and significant effect on the rupiah exchange rate in Indonesia. In the long term, world CPO prices and inflation have a negative and insignificant effect on the rupiah exchange rate in Indonesia, while the money supply has a positive but insignificant effect on the rupiah exchange rate in Indonesia.